Demographic and Clinical Profile of Tuberculous Mastitis Patients at Tebet General Hospital, Jakarta - Pramegia, Desak Ketut Nari Swari; Faried, Rio Putratama Achmad; Setiawan, Kelvin; Rosadi, Bramastha Aires; Lawanto, Terry Renata (JBN (Jurnal Bedah Nasional), 2019)
Keywords: Mastitis, Tuberculous Mastitis, Breast Tuberculosis, Granulomatous Lesions, Extrapulmonal TB